Social Networks as a New Scenario for EFL Speaking Development - de-la-Peña, Cristina; Chaves-Yuste, Beatriz (The International Journal of Interdisciplinary Educational Studies, 2024)
Social networks are incredibly popular among teenagers, and they have proven, when used with appropriate methodologies and strategies, suitable to be applied in educational environments. Considering that social networks aim to entertain, socialize, inform, and teach, it seems convenient to introduce them as complementary tasks in English as a Foreign Language (EFL) instruction. Thus, this work aims to investigate the effect of three popular social networks, (1) TikTok, (2) YouTube, and (3) Spotify, which are focused on the interdisciplinary issue of the responsible use of social networks, specifically on secondary education students’ EFL oral communicative competence and participation. To do so, the speaking skills of a sample of eighty-one ninth-graders were tested when using social networks within the language cooperative learning framework and when being instructed with conventional communicative language teaching tasks. The results confirm the hypothesis that the use of social networks is beneficial for improving EFL oral communicative competence and students’ engagement toward their language learning. Practical implications aimed at including social networks in EFL classes are discussed.
Keywords: social networks; EFL; speaking skill; communicative competence